Mechanical enhancement of zirconia reinforced polyimine nanocomposites. Issue 32 (21st April 2017) - Zhang, Si; Lv, Yanting; Li, Jiayi; Liang, Song; Liu, Zhenning
ABSTRACT: Polymeric nanocomposites have demonstrated superior performance in recent decades, combining the advantages of polymer and nanoparticle fillers. However, nanocomposites of polyimine, a neoteric thermoset material, have been rarely investigated. Herein, a series of polyimine nanocomposites reinforced by zirconia (ZrO2 ) have been fabricated by heat‐pressing under mild conditions. The resultant polyimine nanocomposites show significant enhancements on multiple mechanical properties including tensile strength, toughness, bending strength, and impact strength, whereas the optimal amount of ZrO2 particles for the best performance of a specific property varies. Interestingly, the tensile strength and toughness of the polyimine nanocomposites can be simultaneously increased by 40% and 85%, indicating that the nanocomposites exhibit excellent integration of tensile strength and toughness analogous to natural materials. Hence, a facile and cost‐effective approach to enhance mechanical properties of polyimine has been realized for more applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45183. Abstract :